Influence of reference group on product and brand purchase decisions. - Leong, Mei Mei. (2008)
This study replicates Bearden and Etzel(1982) in the Singapore context with the objective of investigating Singaporeans' product and brand purchase decisions based on the interrelationships between two forms of product. conspicuousness and three types of reference group influence.